2023
DOI: 10.1021/jacs.3c00495
|View full text |Cite
|
Sign up to set email alerts
|

Broad Electronic Modulation of Two-Dimensional Metal–Organic Frameworks over Four Distinct Redox States

Abstract: Two-dimensional (2D) inorganic materials have emerged as exciting platforms for (opto)electronic, thermoelectric, magnetic, and energy storage applications. However, electronic redox tuning of these materials can be difficult. Instead, 2D metal−organic frameworks (MOFs) offer the possibility of electronic tuning through stoichiometric redox changes, with several examples featuring one to two redox events per formula unit. Here, we demonstrate that this principle can be extended over a far greater span with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 79 publications
3
23
0
Order By: Relevance
“…These activation energies imply that thermally activated carriers have a weaker impact on charge transportation in the proton-doped film, while phonon scattering operates vice versa. Despite nanoscale responses in current to external electrical fields in the transistors (Figure S22), the transfer curves indicate a slight amplification of drain currents along the negative gate voltage, suggesting p-type conduction in Cu 3 (HHTATP) 2 , possibly due to the electron-enriched framework facilitated by pendant amines in the linker. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These activation energies imply that thermally activated carriers have a weaker impact on charge transportation in the proton-doped film, while phonon scattering operates vice versa. Despite nanoscale responses in current to external electrical fields in the transistors (Figure S22), the transfer curves indicate a slight amplification of drain currents along the negative gate voltage, suggesting p-type conduction in Cu 3 (HHTATP) 2 , possibly due to the electron-enriched framework facilitated by pendant amines in the linker. , …”
Section: Resultsmentioning
confidence: 99%
“…Toward this effort, the champion materials comprise of planar, tritopic ligands, and studies have probed both the effect of substituting ligating heteroatoms (i.e., substituting S–, O–, and NH– of) and their interplay with ligated metal (i.e., analogues made from Co, Ni, Cu, Fe, Zn, Pd, Pt, etc. ). Previous studies have emphasized the importance of introducing electron-rich chelating motifs (–NH 2 , –SH) to organic linkers to enhance orbital overlaps between the metal cations and linkers. ,, There remains burgeoning interest in designing new tritopic linkers with dissimilar conjugated cores , and points to a central design principle: in-plane metal ligand covalency dictates bulk electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently reported that postsynthetic redox modulation can be extended over an extremely broad range, with four discrete redox states in the 2D MOFs Li x Fe 3 (THT) 2 ( x = 0–3, THT = triphenylenehexathiol, Figure A) . Here, the porosity of this honeycomb framework is critical, as the overall framework topology is unperturbed by the variable counterion loading.…”
Section: Examples Of Redox Chemistry Mediated Control Over Morphology...mentioning
confidence: 98%
“…For example, Nishihara and co-workers synthesized a π-conjugated nanosheet based on Ni–bis­(dithiolene) complexes through a bottom-up method . Later, Ni–bis­(dithiolene)-based MOFs have been synthesized using hexathiolate ligands, showing high conductivity, charge mobility, and metallic character. More recently, Feng and co-workers developed a new 2D c -MOF (denoted as Ni 2 [CuPcS 8 ]) with copper phthalocyanine (CuPc) linked by Ni-bis­(dithiolene) (NiS 4 ) units, which exhibits outstanding pseudocapacitive properties in a conventional nonaqueous electrolyte . Our group further incorporated Ni–bis­(dithiolene) centers into COFs for applications in lithium metal batteries and Li–O 2 batteries. , Although significant progress has been achieved in the development of Ni-bis­(dithiolene)-based 2D MOFs/COFs, the determination of their structures mainly relies on matching experimental powder X-ray diffraction (PXRD) patterns with simulations from hypothetical models.…”
mentioning
confidence: 99%